VIOLATION OF CONVERSATION RULES IN TURN TAKING IN THE SECOND STEP CLASS AT CEC MATARAM - Roy Armansyah; Asbah Asbah; Moh. Fauzi Bafadal (Universitas Muhammadiyah Mataram, 2018)
Abstract: Turn taking is simplest systematic for the organization of turn taking for conversation (Sacks, Schegloff, and Jefferson (1974). In conversation, sometimes the participant violate the rules as they begin to talk, meanwhile the other speakers are still speaking, and none of words and sentences to say in turn. Therefore, the writer was interested to analyze the violation of conversation rules in turn taking in order to investigate kinds of violation of conversation rules in turn taking that happened in the second step class of CEC Mataram, especially in debating activity by using a descriptive qualitative design. Then, the data were collected through video-recording from the second step class members of CEC Mataram. They were about 65 students and one teacher. Based on finding of this study, the writer found out five violations, such as violation of pause, gaps, laps, overlaps, and interruption. The first highest violation was pause violation with 135 times (81.3%) implies that the speaker in debating activity was silence within the turn given. The second one was interruption with 15 times (9.1%) implies that the other speakers began to talk when a speaker was speaking. The third was overlaps with 7 times (4.2%) implies that the speaker spoke at same time. The fourth was gaps with 5 times (3.0%) implies that the speaker did not talk directly when other speaker were given a chance to turn when one speaker was replaced. The fifth was laps with 4 times (2.4%) implies than none options for next turn is used when speaker change, the participant did not indicate backchannel during the debating activity (0% of violation).